Effects of Brazil's Political Crisis on the Science Needed for Biodiversity Conservation - Magnusson, William E.; Grelle, Carlos E. V.; Marques, Márcia C. M.; Rocha, Carlos F. D.; Dias, Braulio; Fontana, Carla S.; Bergallo, Helena; Overbeck, Gerhard E.; Vale, Mariana M.; Tomas, Walfrido M.; Cerqueira, Rui; Collevatti, Rosane; et al. (Frontiers in ecology and evolution, 2018)
The effects of Brazil's political crisis on science funding necessary for biodiversity conservation are likely to be global. Brazil is not only the world's most biodiverse nation, it is responsible for the greater part of the Amazon forest, which regulates the climate and provides rain to much of southern South America. Brazil was a world leader in satellite monitoring of land-use change, in-situ biodiversity monitoring, reduction in tropical-forest deforestation, protection of indigenous lands, and a model for other developing nations. Coordinated public responses will be necessary to prevent special-interest groups from using the political crisis to weaken science funding, environmental legislation and law enforcement.